1988
DOI: 10.2134/agronj1988.00021962008000010019x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Water Use Characteristics of Six Row Crops

Abstract: To help make decisions on shifting of crop species in water management strategies, information is needed on comparative water use characteristics of the principal row crops. The objective of this study was to compare the water use characteristics of six row crops grown in a replicated and randomized field experiment. Crops were corn (Zea mays L.), grain sorghum (Sorghum bicolor (L.) Moench), pearl millet (Pennisetum americanum (L.) Leeke), pinto bean (Phaseolus vulgaris L.), soybean (Glycine max (L.) Merr.), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(46 citation statements)
references
References 3 publications
4
42
0
Order By: Relevance
“…While crop rotations have been used extensively in many dryland systems, the most common crop grown under irrigation in western Kansas is corn (Kenny and Juracek, 2013), often in a CC system. While corn responds well to irrigation, it also requires substantial amounts of water to maximize production (Hattendorf et al, 1988;Howell et al, 1997;Stone et al, 1996;Tolk and Howell, 2001). On average, irrigated corn in Kansas received about 392 mm (ha) -1 of irrigation water in 2012 (Kansas Department of Agriculture, 2012).…”
Section: Core Ideasmentioning
confidence: 99%
“…While crop rotations have been used extensively in many dryland systems, the most common crop grown under irrigation in western Kansas is corn (Kenny and Juracek, 2013), often in a CC system. While corn responds well to irrigation, it also requires substantial amounts of water to maximize production (Hattendorf et al, 1988;Howell et al, 1997;Stone et al, 1996;Tolk and Howell, 2001). On average, irrigated corn in Kansas received about 392 mm (ha) -1 of irrigation water in 2012 (Kansas Department of Agriculture, 2012).…”
Section: Core Ideasmentioning
confidence: 99%
“…The distribution of roots in the soil profile is an important factor in the availability of water and nutrients to plants (Kuchenbuch and Barber, 1987;Rasse and Smucker, 1998). Studies have shown that the superior performance of crops under dry-land conditions is attributed to their ability to extract a significant proportion of water from the deep soil layers (Hattendorf et al, 1988;Angadi and Entz, 2002). The patterns of soil water uptake and depletion are closely correlated with the distribution of root systems (Gardner, 1983;Clothier and Green, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…At the plant level, WUE has been calculated as the ratio of biomass and transpiration in containergrown plants (Blanchet et al 1978;Briggs and Shantz 1914;Green and Read 1983;Morrison and Gifford 1984). Crop WUE has usually been reported in terms of biomass or yield per unit evapotranspiration (Connor et al 1985;Hattendorf et al 1988;Zaffaroni and Schneiter 1989). However, biomass per unit transpiration (i.e.…”
mentioning
confidence: 99%